GRAMMATICAL PROBLEMS IN THE DISCUSSION SECTION OF MASTER THESES - MENTARI, LIDYA RONA; YUNITA, WISMA; HARAHAP, ALAMSYAH (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
The discussion section is the portion of the thesis that presents the research findings by demonstrating an in- depth understanding of the findings, interpreting the findings, and emphasizing their contribution to current knowledge. Additionally, the discussion section is the most difficult component of the thesis. This study sought to identify the most prevalent grammatical errors and their causes in the discussion sections of theses written by English Education postgraduate students at the University of Bengkulu. This study analyzed its data using a mixed methodology. The majority of grammatical problems were investigated quantitatively, while their causes were investigated qualitatively. This study's corpus consisted of thirty master's theses written by English postgraduates who graduated in 2021. The findings revealed that incorrect verbs comprised 65.4%, or 121, of the grammatical errors found in the discussion section of the thesis. These errors were dominated by tense confusion and subject-verb agreement. First-language interference caused the grammatical errors found in the discussion section of the thesis. This study's conclusion provides information about the most common grammatical errors and their possible causes in the thesis discussion section in order to raise the writer's awareness of the significance of grammatical writing in this section.